Enkephalin as a Pivotal Player in Neuroadaptations Related to Psychostimulant Addiction - Mongi-Bragato, Bethania; Avalos, María P.; Guzmán, Andrea S.; Bollati, Flavia A.; Cancela, Liliana M. (Frontiers in Psychiatry, 2018)
Enkephalin expression is high in mesocorticolimbic areas associated with psychostimulant-induced behavioural and neurobiological effects, and may also modulate local neurotransmission in this circuit network. Psychostimulant drugs, like amphetamine and cocaine, significantly increase the content of enkephalin in these brain structures, but we do not yet understand the specific significance of this drug-induced adaptation. In this review, we summarize the neurochemical and molecular mechanism of psychostimulant-induced enkephalin activation in mesocorticolimbic brain areas, and the contribution of this opioid peptide in the pivotal neuroadaptations and long-term behavioural changes underlying psychostimulant addiction. There is evidence suggesting that adaptive changes in enkephalin content in the mesocorticolimbic circuit, induced by acute and chronic psychostimulant administration, may represent a key initial step in the long-term behavioural and neuronal plasticity induced by these drugs.